Sistem Monitoring Limbah B3 Rumah Sakit Berbasis Web dan Mobile - Vina Nurhotijah; Irman Hariman (Journal Data Science, Technology, Informatics and Security, 2025)
The management of hazardous and toxic waste (B3) in hospitals is a crucial aspect to ensure environmental safety and public health. Improper handling of medical waste has the potential to  cause environmental pollution, increase the risk of disease transmission, and create negative impacts on healthcare workers as well as the surrounding community. However, the current  practices of B3 waste management in many hospitals still face several challenges, including error prone manual recording, limited monitoring systems, and a lack of transparency in reporting to relevant stakeholders. This study aims to design and develop a web- and mobile-based monitoring system for B3 waste at Majalaya Regional General Hospital (RSUD Majalaya) to improve efficiency, accuracy, and traceability in waste management processes. The development method applied is Agile with the Scrum framework , enabling the application to be built iteratively and adaptively according to user needs. The developed application is equipped with several main features, including digital waste data recording, waste status monitoring via QR Code, automatic notification when waste accumulation occurs, waste labeling based on categories, and integrated reporting aligned with regulatory standards. The testing results indicate that the system facilitates the recording and monitoring processes, enhances the accuracy of reporting, and supports compliance with government regulations on B3 waste management. With this system, hospital waste  management can be carried out in a more structured, transparent, accountable, and sustainable manner, thereby providing a tangible contribution to environmental protection and public safety.